1999
DOI: 10.1051/aas:1999105
|View full text |Cite
|
Sign up to set email alerts
|

Spectral classification of the cool giants in symbiotic systems

Abstract: Abstract. We derive the spectral types of the cool giants in about 100 symbiotic systems. Our classification is mainly based on near IR spectra in order to avoid the contamination of the spectrum by the nebula and the hot component in the visual region. The accuracy of our spectral types is approximately one spectral subclass, similar to previous near IR classification work, and much better than visual spectral type estimates.Strong, intrinsic spectral type variations (> 2 spectral subtypes) are only seen in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
192
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(211 citation statements)
references
References 35 publications
18
192
1
Order By: Relevance
“…They correspond to Roche lobefilling factors R/R R , which are much too small for circularisation to operate efficiently (i.e., on a time scale comparable to the RGB evolutionary time scale). Interestingly enough, a similar difficulty has been pointed out by Mürset & Schmid (1999) and Mikołajewska (2007) in the context of symbiotic stars. a This number differs from the one quoted by Famaey et al (2005), because we restrict the sample to stars having at least two radial-velocity measurements; b at the level Prob(χ 2 (Vr)) ≤ 0.001.…”
Section: Spectroscopic Binaries (Samples II Iii Iv)supporting
confidence: 69%
“…They correspond to Roche lobefilling factors R/R R , which are much too small for circularisation to operate efficiently (i.e., on a time scale comparable to the RGB evolutionary time scale). Interestingly enough, a similar difficulty has been pointed out by Mürset & Schmid (1999) and Mikołajewska (2007) in the context of symbiotic stars. a This number differs from the one quoted by Famaey et al (2005), because we restrict the sample to stars having at least two radial-velocity measurements; b at the level Prob(χ 2 (Vr)) ≤ 0.001.…”
Section: Spectroscopic Binaries (Samples II Iii Iv)supporting
confidence: 69%
“…All detailed abundance studies performed so far for yellow symbiotics have revealed heavy-element overabundances resembling those observed in S stars (Schmid 1994;Smith et al 1996Smith et al , 1997Pereira & Porto de Mello 1997;Pereira et al 1998;Smith et al 2001;Pereira et al 2003). On the contrary, not a single red symbiotic star from the catalogue of Mürset & Schmid (1999) seems to exhibit the ZrO distinctive spectral features of S-type stars. This puzzling situation is reviewed by .…”
Section: Introductionmentioning
confidence: 94%
“…Mürset & Schmid (1999) give M5.5III -M6III as its stellar type. According to van Belle et al (1999), a typical M5III giant has the following parameters:…”
Section: Tidal Interaction In Mwc 560mentioning
confidence: 99%